A Study on Visualization of Digital Twin Electric Vehicles Based on Gamification: A Simulation Using Game Engines - Jung Tae Kim (Tehnički Glasnik)
This study investigated a methodology for implementing and simulating a digital twin (metaverse) electric vehicle visualization with gamification using a game engine (Unity 3D). This paper is important because it is the first study to visually represent an electric vehicle using a game engine. The core of this study is to analyze the differences between internal combustion and electric vehicles by implementing them in a digital twin, and the KONA model of Hyundai Motor Company, which has two types of engines, was selected. To create the driving roads to compare the performance of the two cars, the terrain was created with Unity Component Terrain. After creating the terrain, configuring the digital twin assets, creating a fuel economy system, setting up object placement and collision settings, and animating, the team created a simple comparison drive that yielded meaningful results. Several gamification elements were applied to motivate players to use the implemented digital twin electric vehicle simulation, increasing curiosity and engagement. Further research will be conducted to add more gamification elements and augment the digital twin experience to make it more engaging and visualize the electric vehicle to increase driver engagement and understanding.